Merancang Sistem Informasi Arsip Surat Pada PT Asuransi Jiwa Syariah Bumiputera Medan Berbasis Web - Afsha Zahara (Teknik Informatika Universitas Pamulang, 2022)
Management of mail archives is an important activity in the company both in managing incoming and outgoing mail. PT Asuransi Jiwa Syariah Bumiputera Medan is a company engaged in sharia-based insurance. In its work activities, PT Asuransi Jiwa Syariah Bumiputera also often conducts correspondence activities, namely obtaining incoming mail and thus also managing outgoing mail, but this letter archive management activity has not been efficient because in managing the archive of the letter it is still done in a manual way such as recording a list of letters that have been submitted. incoming and outgoing mail so that it can cause unexpected obstacles in mail archiving activities. So the purpose of this research is to design a mail archive website so that the mail archive management process becomes more efficient and effective. In making this website, PHP will be used as the programming language, mysql database, and RAD as the system development method. The output of this research is a system that can function to manage mail filing more effectively.